Alice in Numberland / A. K. Balul Karim - Karim, A. K. Bazlul; Time-Life for Children (Firm) (Dhaka : Green book, 1968)
A collection of original stories, poems, riddles, games, and hands-on activities reflecting Alice's adventures in Numberland, where she finds mathematical challenges throughout the magical landscape.
Keywords: Mathematics -- Juvenile literature; Mathematics; Mathematical recreations